Mix Design of Stiff Concrete Mixtures Compacted by Vibration under a Surcharge Load - Sliwinski, Jacek; Brylicki, Witold (Communications - Scientific letters of the University of Zilina, 2002)
In the manufacture technology of products compacted by vibration under a surcharge load, such as paving blocks, it is necessary to use concrete mixtures of consistency outside the range designed for ordinary concrete. Due to the simultaneous effect of vibration and static load the concrete mixture must meet special requirements of consistency and workability. The paper presents two methods of concrete mix design which proved particularly useful for mixtures compacted by vibration under a surcharge load. The former is based on heaping up the aggregate void spaces with cement paste, the latter on coating the aggregate grains with paste.